Обґрунтування та розв’язання задачі відтиску рідкої фази з капілярно-пористого тіла - Білокінь, Ярослав; Дідур, Володимир Володимирович; Bilokin, Yaroslav; Didur, Volodymyr (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті розглянуто задачу математичного опису відтиску рідкої фази з деформівного капілярно-пористого тіла в умовах пресування. Показано, що складність процесу зумовлена одночасною зміною тиску в рідині та скелеті твердої фази, а також зміною проникності пористого середовища внаслідок його ущільнення. Для опису процесу запропоновано два підходи: розв’язання диференціального рівняння відтиску за сталого коефіцієнта напірної провідності та розв’язання нелінійної задачі зі змінним коефіцієнтом, який залежить від тиску. Для побудови розв’язку використано метод Бубнова-Гальоркіна, поліноми Лежандра, матричний апарат і чисельне інтегрування методом Ейлера. Встановлено, що модель зі сталим коефіцієнтом напірної провідності дозволяє описати загальні закономірності процесу, однак не забезпечує потрібної точності. Більш адекватним є підхід зі змінним коефіцієнтом напірної провідності, для якого застосовано підстановку Кірхгофа та отримано нелінійну систему звичайних диференціальних рівнянь. Результати можуть бути використані для аналізу процесів пресування олійних матеріалів і для інженерного обґрунтування параметрів шнекових пресів. /// EN: Oily material during pressing is a complex multicomponent system in which compaction of the solid phase, redistribution of load between the liquid and the skeleton, filtration of the liquid phase and change in permeability of the capillary-porous structure occur simultaneously. It is this deformation variability of the medium that complicates the mathematical description of the impression process and does not allow us to limit ourselves to simplified models with constant parameters. The aim of the work is to substantiate the mathematical formulation and solution of the problem of liquid phase imprinting from a capillary-porous body taking into account the deformation of the porous medium, as well as to compare approaches for a constant and variable pressure conductivity coefficient. The article substantiates and solves the problem of liquid phase expression from a capillary-porous body under pressing conditions. It is shown that the main difficulty of the process lies in the coupled evolution of liquid pressure, solid skeleton pressure, and permeability of the deformable porous medium. Two approaches are considered: a linear model with a constant pressure-conductivity coefficient and a nonlinear model with a pressure-dependent coefficient. The Bubnov–Galerkin method, Legendre polynomials, matrix transformations, Kirchhoff substitution, and Euler numerical integration were applied to obtain the solution. It was found that the constant-coefficient model reproduces the general trend of pressure redistribution but does not provide sufficient accuracy for describing the real pressing process. The nonlinear formulation with a variable pressure-conductivity coefficient provides a more adequate description of liquid phase expression from the porous material. The obtained results can be used for the analysis and engineering design of screw presses and other equipment for oil-bearing material processing.
Justification and solution of the problem of liquid phase printing from a capillary-porous body
Keywords: капілярно-пористе тіло; відтиск рідкої фази; пористе середовище; пресування; напірна провідність; математична модель; шнековий прес; capillary-porous body; liquid phase imprint; porous medium; pressing; pressure conductivity; mathematical model; screw press